PEGEMBANGAN DAN VALIDASI METODE HEPARIN ATAU ENOKSAPARIN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI PASANGAN ION - Astuti, Engrid Juni; Hidayati, Ika Ratna; Ibrahim, Slamet; Zulfikar, Muhammad Ali (School of Pharmacy Institut Teknologi Bandung, 2025)
One of the drugs used to treats and prevents COVID-19 thromboembolic problems is heparin or enoxaparin sodium. Heparin and enoxaparin have the side effect of bleeding when used, so monitoring of therapy is necessary. This present study aims to validate an ion pair high-performance liquid chromatography (HPLC) condition to analyse the adsorption of heparin or enoxaparin at molecularly imprinted polymer (MIP) after synthesis. The chromatographic system consists of a C8 column with a Diode Array Detector (DAD). The optimal chromatographic condition was obtained using mobile phase A (300mM NaCl + 10mM tetra n-butyl ammonium hydroxide) and mobile phase B (acetonitrile) under gradient elution, and 100 µl injection volume. The heparin or enox was detected at 231 nm, generating symmetrical peaks and good separation in 4.1 minutes after injection. The method indicated good selectivity with a resolution of 3.49 for heparin and 3.74 for enox. A linear detector response with R2 of 0.9965 and 0.9994 for heparin and enox. The method yields good precision and good accuracy. The proposed method has met the method validation requirements for adsorption heparin or enox analysis before using validation in biological samples.